(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Abstract: Introduction: CoVID-19 (Coronavirus disease) pandemic has involved the whole globe and exposed the limitation of health care system of different countries. Although , different countries have introduced various modalities to protect both general population and health care provider to counter this world health crises but still lacked immensely leading to higher probability of contracting disease .We followed standard protocols and sharing our experience of 2688 cases. Physiological stress compromise immunity of patient result in increasing complications .We also determined rate of mortality and infection in covid and non- covid patients. Methods: Clinical data of 2688 patients was assessed retrospectively who underwent orthopaedics surgeries during the period of COVID-19 wave in Pakistan at Ghurki Trust Teaching Hospital in Lahore, between march 19 to June 30, 2020.Hospital protocol for Covid screening was followed including questionnaire soughting respiratory symtoms,travel history, contact history and investigations like CBC, CRP and chest radiography. HRCT and nasopharyngeal PCR swabs are only performed in highly suspicious patients. Results: Out of 92 highly suspicious patients ,71 came out to Covid-19 positive. Group A patients were significantly younger compared to group B (32.1±18.9 vs. 40.6±26.9, p value 0.008). There was male preponderance in both groups. Lower limb trauma constituted more than half of workload. Majority of patients were given spinal anaesthesia. Operative time was significantly higher in group B (p value <0.0001). Post-operatively, proportion of patients requiring admission to ICU was significantly higher for patients who were COVID positive (p-value 0.002). In 30 day post-operative period 3 (4.2%) COVID positive and 59 (2.3%) COVID negative patients died (p-value 0.22). Conclusion: In this retrospective surgical audit , mortality and complications were equivocal when Covid positive patients were matched with non Covid patients. Therefore ,it is suggested we should continue treating patients .However, protocols and necessary preventive measures should be followed.